Quality of Work Life in the area of Public Safety: a diachronic perspective of smell perceptions and their implications for the health of employees - Cavedon, Neusa Rolita (Organizações & Sociedade, 2014)
The concept of quality of work life under a multifaceted dynamics involves cultural, social, economic, political and temporal aspects, in addition to the notions of physical and emotional health. It creates a sensation that can be interpreted from a diachronic, personal and social perspective, as the provider of well-being condition. Therefore, the purpose of this article is to identify how the quality of work life is affected as a result from smell perceptions and what the implications are for the health of employees of Department of Criminalistics, which integrates the General Institute of Forensics of Rio Grande do Sul. The methodology chosen to carry out this research was ethnography, with participative observation and interviews. The data analysis focused on the articulation of theoretical bases with emic categories and ethical interpretation, revealing that the ‘smell of death’ is regarded by the employees as something hard tolerate. The cigarette is a way of alleviating the putrid odors. The ingestion of certain foods is equally affected by the smell and view of the crime scene. In this context, the use of masks and ergonomically adequate clothing is a sine qua non condition.